Audit Committee and Timely Reporting: Evidence From Turkey - Merter, Abdullah Kursat; Özer, Gökhan (Sage Publications Inc, 2024)
This paper seeks to examine whether the characteristics of the audit committee impact the timely reporting represented by audit report lag (ARL), firm-based abnormal audit report lag (FAARL), and industry-based audit reports lag (IAARL). The sample of the study includes mostly hand-collected 2,284 firm-year observations obtained from Turkey's listed non-financial companies. Main regression results show that audit committee gender diversity, meeting frequency, and independence are negatively associated with timely reporting. Furthermore, additional analysis indicates the negative association between timely reporting and the audit committee effectiveness indexes created by the coexistence of the audit committee. Also, an interaction effect between audit committee independence and gender diversity concerning the timeliness of financial reporting has been documented. The use of fixed effects estimators and two-step system GMM estimator also supported the main results. This paper aims to provide concrete contribution to the literature by examining timely reporting in an emerging market like Turkey. The results suggest that regulatory bodies and companies should review the audit committee structure to better timely reporting and reduce firm and industry-based abnormal delays. This study aims to understand how the characteristics of audit committee influence the timeliness of financial reporting, as represented by three measures: audit report lag, firm-based abnormal audit report lag, and industry-based audit report lags. The research is based on data from 2,284company-year observations, mainly collected by hand from non-financial companies listed in Turkey. To analyze the data, the study utilized regression models and other advanced statistical techniques. The findings show that more diverse (in terms of gender), frequent-meeting, and independent audit committees tend to report more promptly. Additionally, when certain audit committee characteristics combine, there is an even stronger tendency toward timely reporting. These results imply that for better and more timely reporting, companies, especially in emerging markets like Turkey, might benefit from audit committees that are diverse, independent, and meet frequently. Regulatory bodies might also consider these findings when setting guidelines for audit committee structures.
Keywords: gender diversity; financial reporting timeliness; audit committee; audit report lag; interaction analysis